Leadership Strategy of Village Head in Developing Village Information Systems (Case Study in Village Jia Sape District Bima Regency) - Hendra Hendra; Muhammad Taufiq; Muhammad Nur Rijal; Rusli Rusli; Arif Budiman; Faida Faida (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Digital transformation in village governance has emerged as a strategic imperative for enhancing public service quality, administrative efficiency, transparency, and accountability at the local government level. Within this context, the Village Information System (VIS) serves as a critical instrument for supporting data-driven governance and citizen-oriented service delivery. However, the successful development and implementation of VIS are influenced not only by technological infrastructure but also by leadership capacity and organizational readiness. This study aims to examine the leadership strategies employed by the Head of Jia Village, Sape District, Bima Regency, in the development of the Village Information System. A qualitative case study approach was adopted, with data collected through in-depth interviews, participant observation, and document analysis involving village officials, VIS operators, representatives of the Village Consultative Body (BPD), and community members. Data were analyzed using an interactive model comprising data condensation, data display, and conclusion drawing and verification. The findings reveal that the Head of Jia Village adopted adaptive, participatory, and service-oriented leadership strategies to facilitate VIS development. These leadership practices were manifested across five dimensions of public service quality: (1) tangibles, reflected in the provision of digital infrastructure and supporting service facilities; (2) reliability, demonstrated through efforts to strengthen the competence and professionalism of village officials; (3) responsiveness, evidenced by the ability to address community needs promptly through both conventional and digital communication channels; (4) assurance, reflected in the enhancement of trust, service ethics, and institutional credibility; and (5) empathy, demonstrated through citizen-centered service approaches that prioritize accessibility and inclusiveness. Despite these achievements, VIS utilization remains suboptimal due to limited levels of digital literacy among community members, resulting in a continued preference for face-to-face service interactions. This study concludes that leadership plays a pivotal role in advancing digital transformation within village governance. The effectiveness of VIS development depends not only on technological readiness but also on the capacity of local leaders to integrate digital innovation with human resource development and community participation. The findings contribute to the growing body of knowledge on digital governance and rural leadership by highlighting the significance of adaptive and transformational leadership in sustaining digitalization initiatives at the village level.